Use of Functionalized Biomaterials with Bioactive molecules in Biomedical Engineering - Reyes-Blas, H.; Olivas-Armendáriz, I.; Martel-Estrada, S. A.; Valencia-Gómez, L. E. (Revista Mexicana de Ingenieria Biomedica, 2019)
The paper exposes the importance of the use of bioactive molecules for the functionalization of biomaterials. For this reason, a review of current and relevant research was carried out in various data searchers, including the di-fferent types of bioactive materials and molecules used to elaborate functionalized biomaterials, with emphasis on the processes and their properties. It was found that the process of functionalization or modification of the surface expands the path to adapt the biomaterial according to the physiological environment of living cells. This process improves the structure and functions of the designed tissues and organs. There are a variety of methods and bioac-tive molecules available for the functionalization of biomaterials, depending on the way in which the cells or tissues are regenerated. Among the different materials for the manufacture of biomaterials, biomolecules such as proteins, lipids, carbohydrates, among others, are one of the most used options due to the similarity of these with the bio-logical systems of the human body. Finally, the paper also integrates some of the most promising applications of bioactive molecules incorporated into biomaterials.